Corporate constructed and dissent enabling public spheres: differentiating dissensual from consensual corporate social responsibility - Whelan, Glen (Springer Verlag, 2013)
I here distinguish dissensual from consensual corporate social responsibility (CSR) on the grounds that the former is more concerned to organize (or portray) corporate-civil society disagreement than it is corporate-civil society agreement. In doing so, I first conceive of consensual CSR, and identify a positive and negative view thereof. Second, I conceive of dissensual CSR, and suggest that it can be actualized through the construction of dissent enabling, rather than consent-oriented, public spheres. Following this, I describe four actor-centred institutional theories-i.e. a sociological, ethical, transformative and economic perspective, respectively-and suggest that an economic perspective is generally well suited to explaining CSR activities at the organizational level. Accordingly, I then use the economic perspective to analyse a dissent enabling public sphere that Shell has constructed, and within which Greenpeace participated. In particular, I explain Shell's employment of dissensual CSR in terms of their core business interests; and identify some potential implications thereof for Shell, Greenpeace, and society more generally. In concluding, I highlight a number of ways in which the present paper can inform future research on business and society interactions.